Severe community-acquired pneumonia caused by Chlamydia abortus in China: a case report - Yang, Qiong-Fang; Shu, Cai-Min (Frontiers in Medicine, 2024)
Background: Chlamydia abortus causes abortions in ruminants; it can also cause miscarriages and stillbirths in pregnant women. However, it rarely causes pneumonia in humans. Here, we report a case of severe community-acquired pneumonia caused by C. abortus.On admission to our hospital, a 74-year-old woman reported that she had had a fever, cough, phlegm in her throat, and shortness of breath for 10 days. In the local hospital, she was initially diagnosed with community-acquired pneumonia and treated with piperacillin-tazobactam for 4 days. However, her condition worsened, and she was therefore transferred to our hospital.On arrival at our emergency department, she was diagnosed with severe community-acquired pneumonia and treated with a high-flow nasal cannula and meropenem; she was then transferred to the Department of Respiratory Medicine. There, her condition continued to worsen despite continued treatment with the high-flow nasal cannula and omadacycline.After 24 hours and emergency tracheal intubation, the patient was sent to the intensive care unit (ICU) for further treatment. The doctors in the ICU again adjusted the treatment, this time to meropenem along with mechanical ventilation; they also instituted methylprednisolone, ulinastatin, nadroparin calcium, and human immunoglobulin. In addition, bronchoalveolar lavage fluid was sent for metagenomic next-generation sequencing (mNGS). Subsequent mNGS suggested the presence of C. abortus, sequence number 5072; we therefore discontinued the meropenem and implemented a combination of doxycycline and moxifloxacin. After 8 days of treatment in the ICU, the patient's condition improved; she was then extubated and, 3 days later, transferred back to the respiratory medicine department. The respiratory physician continued to administer doxycycline and moxifloxacin for 4 days, after which the patient was discharged with medication. A month later, a repeat computed tomography (CT) scan of the chest suggested that the lesions in both lungs had been largely absorbed. Conclusions: C. abortus can occasionally cause pneumonia in humans and, rarely, severe, life-threatening pneumonia. mNGS is uniquely suited for the early detection of this unusual infection. The combination of doxycycline and quinolones has been shown to be effective in severe pneumonia caused by C. abortus.